211k views
5 votes
(I RAISED THE POINTS AND THIS IS MULTIPLE CHOICE PLEASE TRY TO EXPLAIN WHY YOU GOT THAT ANSWER THANKS~~)

what is the 11th term in the sequence: an= -6n+13?

a)53
b) -79
c) -53
d)79

User Gdlmx
by
5.0k points

2 Answers

7 votes

Answer:

53

Explanation:

You are asking for a(11), having provided the general formula

a(n) = -6n + 13.

Substituting 11 for n, we get:

a(11) = -6(11) + 13 = 13 - 66 = 53

The 11th term is 53.

User Griff
by
5.0k points
3 votes

Ok so if you want the 11th term you have to put 11 instead of n so it’s

-6*11+13=-53